Surrendering control, or nothing to lose: Parents' preferences about participation in a randomised trial of childhood strabismus surgery. (August 2015) - Buck, Deborah; Hogan, Vanessa; Powell, Christine J; Sloper, John J; Speed, Chris; Taylor, Robert H; Tiffin, Peter; Clarke, Michael P
Background: Intermittent exotropia is the most common form of divergent strabismus (squint) in children. Evidence regarding its optimum management is limited. A pilot randomised controlled trial has recently been completed (Surgery versus Active Monitoring in Intermittent Exotropia trial) to determine the feasibility of a full randomised controlled trial. Purpose: To identify drivers for and barriers against parents' participation in Surgery versus Active Monitoring in Intermittent Exotropia and to seek their views on information received, the need for randomisation, and enhancing acceptability. Methods: Multiple method qualitative study using semi-structured telephone interviews to explore parents' motivations and trial screening logs to provide an indication of common barriers. Exploratory thematic analysis identified key themes. Results: A total of 48 interviews were conducted (14 participants; 34 non-participants). Barriers included no desire for surgery/preference to 'wait and see', wanting surgery immediately, feeling uncomfortable about 'surrendering control' over decision-making/being managed 'at random', lack of confidence in the effectiveness of surgery, believing the risks outweighed the benefits, and lack of trust. Drivers included desiring surgery, 'nothing to lose', benefits offsetting the risks, and being in a trial would result in better care. Some also mentioned 'doing their bit' for research. Suggestions for enhancing acceptability included allowing choice of treatment group, giving more time for decision-making, expanding on information given, and improving communication. Many felt the necessity of randomisation was adequately explained, but there was some indication that it was misunderstood. Information extracted from the screening logs of 80/89 eligible non-participants indicated the most prevalent barrier was not wanting surgery/preferring to observe (56%), followed by desiring surgery straightaway (15%). Opposition to randomisation/wanting to retain control was recorded in 9% of cases as was the belief that the child's squint was not severe enough to warrant surgery. Limitations: Interviews were not audio-recorded. Not all who consented to interview could be contacted, although the response/contact rate was good (48/62). A few parents did not provide reasons for refusing the trial. Conclusion: Opposition to surgery and concerns about surrendering control were common obstacles to participation, whereas parents keen for their child to undergo the operation but happy to defer tended to embrace a 'nothing to lose' attitude. Many non-participants would have consented if allowed to choose group, although most of these would have chosen observation. While most parents felt happy with information given and that randomisation was adequately explained, it is of concern that there may be some misunderstanding, which should be addressed in any trial. These findings will inform future trials in childhood exotropia, for example, consideration of preference arms and improving communication. Lessons learnt from the Surgery versus Active Monitoring in Intermittent Exotropia trial could prove valuable to paediatric and surgical trials generally.